2001
DOI: 10.1097/00005537-200110000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Computed Tomography Diagnosis of Non‐Recurrent Inferior Laryngeal Nerve

Abstract: It was possible to predict an aberrant subclavian artery by identifying the brachiocephalic artery and position of the right subclavian artery on the CT film of the neck. When an anomaly of the subclavian artery is thus preoperatively detected, NRILN can be preoperatively predicted, which likely will enable prevention of vocal cord paralysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 17 publications
2
62
0
3
Order By: Relevance
“…Dysphagia is the main symptom of arteria lusoria. Several preoperative diagnostic investigations for vascular anomaly have been described, including CT, barium swallow, and ultrasonography (Nagayama et al 1994;Watanabe et al 2001;Hermans et al 2003, Devèze et al 2003. In this patient, evaluation of preoperative CT including the neck to mediastinum was very useful and enabled the operation to be performed safely and fast.…”
Section: Discussionmentioning
confidence: 90%
“…Dysphagia is the main symptom of arteria lusoria. Several preoperative diagnostic investigations for vascular anomaly have been described, including CT, barium swallow, and ultrasonography (Nagayama et al 1994;Watanabe et al 2001;Hermans et al 2003, Devèze et al 2003. In this patient, evaluation of preoperative CT including the neck to mediastinum was very useful and enabled the operation to be performed safely and fast.…”
Section: Discussionmentioning
confidence: 90%
“…Some studies have reported 100% accuracy for ultrasonography in detecting NRLN-associated vascular anomalies [19,20] , allowing earlier nerve identification and prevention of injuries [19] . Computed tomography is also being used as a routine examination before thyroid surgery in some institutions for this purpose [5] . Nevertheless, systematic preoperative use of imaging methods is not yet recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative ultrasound or computed tomography may provide clues about the existence of an NRLN, thus avoiding iatrogenic injury to the nerve [5] .…”
Section: Introductionmentioning
confidence: 99%
“…The availability of a preoperative diagnosis of NRLN may reduce the risk of accidental nerve injuries (9)(10)(11)(12).…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Several techniques for preoperative identification of this anomaly have been proposed (chest X-ray, barium swallowing test, CT, MR, esophageal endoscopy, and IONM) (7,11,(14)(15)(16)(17)(18)23,(30)(31)(32) but their routine use is limited by the variable diagnostic accuracy, invasiveness, and costs.…”
Section: Proposed In 1972 Stewart Et Al (24) Described Two Types Ofmentioning
confidence: 99%